2009
DOI: 10.1210/jc.2009-0290
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulable State in Cushing’s Syndrome: A Systematic Review

Abstract: Available studies suggest a high risk of venous thrombosis in patients with Cushing's syndrome. Glucocorticoid-induced hypercoagulability as well as surgery and obesity almost certainly contribute to this thrombotic tendency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
150
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 42 publications
6
150
1
1
Order By: Relevance
“…The authors confirmed that there is an increased risk of unprovoked and post-operative venous thromboembolism in patients with Cushing's syndrome (82). Glucocorticoid-induced hypercoagulability as well as surgery and obesity, conditions that are commonplace in patients with Cushing's syndrome, almost certainly contributes to this prothrombotic tendency.…”
Section: Cushing's Syndromementioning
confidence: 72%
See 2 more Smart Citations
“…The authors confirmed that there is an increased risk of unprovoked and post-operative venous thromboembolism in patients with Cushing's syndrome (82). Glucocorticoid-induced hypercoagulability as well as surgery and obesity, conditions that are commonplace in patients with Cushing's syndrome, almost certainly contributes to this prothrombotic tendency.…”
Section: Cushing's Syndromementioning
confidence: 72%
“…Thus, future larger clinical and intervention studies are required to provide more definitive information on the clinical relevance and the effects of the pharmacologic treatment of the hormonal dysfunction on the abnormalities of coagulation and fibrinolysis in these endocrine disorders. At present, there is a general agreement that a high risk of venous thromboembolism is present in patients with active Cushing's syndrome, and that thromboprophylaxis with low-molecular-weight heparin should be (routinely) considered in patients with this disorder undergoing surgery (82). Although the available data are controversial and more extensive studies are necessary, prophylactic anticoagulation might be also recommended in older patients with hyperthyroidism and atrial fibrillation in the presence of other heart disease, hypertension, or other important risk factors for embolization (148).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent VTE in these patients, early VTE (particularly DVT) screening and diagnosis are very important [10,11]. VTE is a frequent complication in patients with CS, especially during and after surgery [2,3], and thromboprophylaxis has been recommended for patients with active CS. However, thromboprophylaxis carries some inherent risks such as bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…Non provoked venous thromboembolism risk is doubled in CS. Risk of postoperative venous thromboembolism is varied between 0 and 5.6% (43). High levels of fibrinogen, factor VIII, factor IX, von Willebrand factor and the evidence of enhanced thrombin generation are the suggested reasons for glucocorticoid induced hypercoagualopathy.…”
Section: Prothrombotic Statementioning
confidence: 99%